Third Mission and identity in a Catholic university: The Universidad de La Sabana case - Juan F. Córdoba-Marentes (Church, Communication and Culture)
This case study examines the comprehensive strategies employed by Universidad de La Sabana to align its Third Mission with its Catholic identity after a media and public opinion crisis in 2015. The crisis, triggered by controversial remarks from a university professor during a national debate on same-sex adoption, underscored the necessity for the university to assert its institutional values while navigating the complexities of public scrutiny. In response, the university undertook organizational realignments, including the establishment of new strategic committees, the development of communication training programs, and the enhancement of its Legal Clinic’s role. These initiatives were designed not only to mitigate reputational risks but also to reinforce the university’s capacity to engage successfully in public discourse. Additionally, the university launched other impactful public initiatives, which further strengthened its legitimacy and influence on broader societal issues. The findings of this study provide a detailed account of these strategies and their outcomes, offering insights for other institutions facing similar challenges. This study contributes to the literature on crisis management in higher education and highlights the critical importance of aligning institutional identity with public engagement, particularly in a polarized societal context.